PENGARUH SIKAP MAHASISWA AKUNTANSI DAN MAHASISWA MANAJEMEN TERHADAP PENGOLAHAN DATA SKRIPSI DALAM MENGGUNAKAN PROGRAM STATISTICAL PROGRAM FOR SOCIAL SCIENCE ( SPSS) - Nasyaroeka, Jhon (Jurnal Manajemen Magister Darmajaya, 2017)
The influence of the attitude of accounting students and management students in processing the data on thesis or final project using statistical program that is SPSS has a significant influence. This is because the influence of the attitude of accounting students and management students have a big influence attitude on the use of statistical program SPSS. In this study there are more students accounting attitude using statistics program especially SPSS. This is because accounting students prefer statistics program because it is more accurate data processed and faster if the data with statistical program.Ini can be seen from the results of questionnaire.Keyword: Influence of the attitude, SPSS, Statistics Program